Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan Di Pdam Kabupaten Sumenep - Moh. Faisol Rahman; Muhammad Mansur; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
The purpose of this study is used to determine how the influence of work discipline and work environment on work performance. In this study, there are three variables used, namely the variable work discipline and work environment which are independent variables, while work performance is the dependent variable. Whereas in this study the number of respondents was 44 employees. The data collection method is done by using a questionnaire. The analytical method used is multiple linear regression analysis. The results showed that work discipline and work environment simultaneously had an effect on work performance. Work discipline affects work performance and work environment affects work performance.Keywords: Work Discipline, Work Environment, Work Performance.